Assessment of the Diameter of Thoracic Aorta by Computed Tomography of Chest - Koju, Anish; Joshi, Birendra Raj (Nepalese Journal of Radiology, 2018)
Introduction: The aim of this study was to assess the diameters of thoracic aorta of normal Nepalese people by using computed tomography scans of chest and to correlate the diameters with the patient’s age, gender, height, weight and BMI. Methods: This prospective study was performed in the Department of Radiology and Imaging,TUTH. Data were collected over the period of 4 months from June to September 2017 with the total of 99 patients who underwent contrast enhanced CT of chest in the tertiary hospital. Results: The diameter of thoracic aorta was found to be maximum at the level of aortic valve sinus (3.23±0.36 cms), minimum at the level of diaphragm(2.20±0.31 cms), and mean diameter of ascending aorta was found to be 2.73±0.27 cm. Conclusion: This study concluded that the diameter of thoracic aorta increased with increase in age and vice versa. The diameter of thoracic aorta decreased in the tapering fashion distally from the aortic valve sinus